MicroRNA biogenesis: regulating the regulators - Finnegan, Emily F.; Pasquinelli, Amy E. (Critical reviews in biochemistry and molecular biology, 2013)
MicroRNAs (miRNAs) function as 21-24 nucleotide guide RNAs that use partial base-pairing to recognize target messenger RNAs and repress their expression. As a large fraction of protein-coding genes are under miRNA control, production of the appropriate level of specific miRNAs at the right time and in the right place is integral to most gene regulatory pathways. MiRNA biogenesis initiates with transcription, followed by multiple processing steps to produce the mature miRNA. Every step of miRNA production is subject to regulation and disruption of these control mechanisms has been linked to numerous human diseases, where the balance between the expression of miRNAs and their targets becomes distorted. Here we review the basic steps of miRNA biogenesis and describe the various factors that control miRNA transcription, processing, and stability in animal cells. The tremendous effort put into producing the appropriate type and level of specific miRNAs underscores the critical role of these small RNAs in gene regulation.